Radiation Dosimetry of Theragnostic Pairs for Isotopes of Iodine in IAZA - Hans-S. Jans; Daria Stypinski; Piyush Kumar; John R. Mercer; Stephen A. McQuarrie; Alexander J. B. McEwan; Leonard I. Wiebe (Pharmaceutics, 2022)
Theragnostic pairs of isotopes are used to infer radiation dosimetry for a therapeutic radiopharmaceutical from a diagnostic imaging study with the same tracer molecule labelled with an isotope better suited for the imaging task. We describe the transfer of radiation dosimetry from the diagnostic radioiodine isotope 123I, labelled for the hypoxia tracer molecule iodoazomycin arabinoside ([123I]IAZA), to isotopes 131I (therapeutic) and 124I (PET imaging). Uncertainties introduced by the dissimilar isotope half-lives are discussed in detail. Radioisotope dosimetries for [123I]IAZA were obtained previously. These data are used here to calculate residence times for 131I and 124I and their uncertainties. We distinguish two cases when extrapolating to infinity: purely physical decay (case A) and physical decay plus biological washout (case B). Organ doses were calculated using the MIRD schema with the OLIDNA/EXM code. Significant increases in some organ doses (in mSv per injected activity) were found for 131I and 124I. The most affected organs were the intestinal walls, thyroid, and urinary bladder wall. Uncertainty remained similar to 123I for case A but considerably greater for case B, especially for long biological half-lives (GI tract). Normal tissue dosimetries for IAZA must be considered carefully when substituting isotope species. A long biological half-life can significantly increase dosimetric uncertainties. These findings are relevant when considering PET imaging studies with [124I]IAZA or therapeutic administration of [131I]IAZA.